Corporate Governance Mechanism On Banking Financial Performance - Umyana, Siti (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
Every year Islamic banking has progressed quite rapidly to compete in the financial sector. By offering lower interest rates and some tips that attract the attention of Islamic banking consumers, it is enough to attract people to use the financial services of the bank. However, it should also be noted that every bank, be it Sharia or general, has various strategies to attract the attention of customers who will use the bank's services. To make customers more comfortable and interested in using the services of a bank, there are several mechanisms that are applied, and in this study the researchers used the corporate governance mechanism as the independent variable and the financial financial performance variable as the dependent variable. By using a quantitative descriptive approach by distributing several questionnaires to respondents who have been determined by the researcher to get results on a Likert scale. From the results of research processed using the help of several SPSS 21 applications, it shows that directors and institutional ownership have a positive influence on the performance of Islamic banks.